1997
DOI: 10.1007/bf03164811
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in nuclear cardiology in the study of coronary artery disease

Abstract: A variety of new radiopharmaceutical agents have been introduced to probe myocardial function in vivo. This review will introduce these new techniques which have recently been available in Japan. Tc-99m perfusion imaging agents provide excellent myocardial perfusion images which may enhance diagnostic accuracy in the study of coronary artery disease. In addition, greater photon flux from the tracer permits simultaneous assessment of regional perfusion and function with use of first-pass angiography or ECG-gate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 101 publications
1
6
0
Order By: Relevance
“…BMIPP distribution is homogeneous. The result of the relatively homogeneous distribution of BMIPP in this study is in accordance with a previous study [23]. The BMIPP compound is designed for SPECT imaging, which requires long myocardial retention of the tracer for good image quality.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…BMIPP distribution is homogeneous. The result of the relatively homogeneous distribution of BMIPP in this study is in accordance with a previous study [23]. The BMIPP compound is designed for SPECT imaging, which requires long myocardial retention of the tracer for good image quality.…”
Section: Discussionsupporting
confidence: 87%
“…In an ischemic condition, discordant 123 I-BMIPP uptake less than that of perfusion tracer may reflect decreased pO 2 levels and tissue ATP concentrations, leading to a switch from fatty acid to glycolytic oxidation [26]. 123 I-BMIPP provides valuable information on myocardial metabolism reflecting mitochondrial function [23]. Therefore, reading BMIPP images using an appropriate standard database in comparison with perfusion imaging is vitally important [12,26].…”
Section: Discussionmentioning
confidence: 99%
“…BMIPP defect size in subacute phase of myocardial infarction correlated well with the risk area revealed by contrast ventriculography or echocardiography [56,61], and the area with BMIPP reduction 1 week after the onset of myocardial infarction corresponded well to the area with perfusion defect which was demonstrated before revascularization therapy at admission [62]. These observations suggested that BMIPP imaging obtained in subacute phase of myocardial infarction can be called "ischemic memory imaging" because it reflects prior ischemic damage or metabolically stunned myocardium even after the restoration of perfusion abnormality [56,63,64]. In chronic phase of myocardial infarction, mismatched uptake of BMIPP less than thallium is not an uncommon finding.…”
Section: Acute Myocardial Infarctionmentioning
confidence: 78%
“…As an example, fatty acids have been used for following the kinetics of biological processes, such as membrane transport, blood flow, and cardiac fatty acid metabolism . [ω‐ 11 C]Palmitate is a well‐established PET tracer to probe myocardial fatty acid metabolism . Synthesis of [ω‐ 11 C]palmitate involves incorporation of 11 C‐alkyl iodide employing Grignard reaction, Suzuki cross coupling, organocopper chemistry, or functionalized copper–zinc reagent (Scheme ) …”
Section: Preparation and Labeling Of Endogenous Compoundsmentioning
confidence: 99%